Children’s Perceived Economic Disadvantage and Social Relationships in School: Family Relationships as a Mediating Factor - Hautala, Helena; Lehti, Hannu (Springer Science and Business Media LLC, 2025)
We investigate how perceived economic disadvantage is associated with social relationships in school among children aged 9–14 years and the mediating effect of family relationships in the association. We measure economic disadvantage through both perceived financial concerns and the child’s estimate of the amount of money he or she has compared to friends. Social relationships are measured through the experience that teachers care and trust that other children will help if needed. Family relationships are measured through three variables measuring a child’s experiences of communication with parents and having a good time with family. As data, we use the Finnish sub-survey from the third wave of the international survey Children’s Worlds, The International Survey of Children’s Well-being (ISCWeB) for 2018–2019 (N = 1684), which we analyze using linear probability regression models. Results show that both measured dimensions of perceived economic disadvantage are negatively associated with the experience that teachers care and the trust that other children help. Family relationships mediate the association of financial concerns with relationships with both teachers and other children in school. Having less money than friends is associated with relationships with both teachers and other children, regardless of family relationships. Attention should be paid to the socio-emotional well-being of economically disadvantaged children in school, especially children who are exposed to vulnerability in family relationships as well. It is important not only to promote economic equality but also to be aware of hierarchies built on economic grounds among children.